2021
DOI: 10.1002/anie.202108766
|View full text |Cite
|
Sign up to set email alerts
|

Proton Traffic Jam: Effect of Nanoconfinement and Acid Concentration on Proton Hopping Mechanism

Abstract: The properties of the water network in concentrated HCl acid pools in nanometer-sized reverse nonionic micelles were probed with TeraHertz absorption, dielectric relaxation spectroscopy, and reactive force field simulations capable of describing proton hopping mechanisms.W ei dentify that only at acritical micelle size of W 0 = 9dosolvated proton complexes form in the water pool, accompanied by ac hangei n mechanism from Grotthuss forwards huttling to one that favors local oscillatory hopping.This is due to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 75 publications
3
23
0
Order By: Relevance
“…In principle, also an intermediate [as is of relevance in formazan synthesis (Hegarty and Scott, 1966;Hegarty and Scott, 1967;King and Murrin, 2004)] with two azo groups and the H atom at the interjacent C atom is conceivable, but much less stable than the formazan tautomers (Buemi et al, 1998) (see also Supplementary Figure S7). However, the transfer might occur via a proton wire mechanism, i.e., in a Grotthusstype fashion (Agmon, 1995;Miyake and Rolandi, 2015;Adams et al, 2021) as was found in water but also identified in other protic solvents (Stoyanov et al, 2008;Fujii et al, 2018;Long et al, 2020). Hence, the isomerization involving proton transfer should only be possible in protic solvents or in aprotic solvents containing at least traces of protic cosolvents.…”
Section: Interconnection Among Isomersmentioning
confidence: 89%
“…In principle, also an intermediate [as is of relevance in formazan synthesis (Hegarty and Scott, 1966;Hegarty and Scott, 1967;King and Murrin, 2004)] with two azo groups and the H atom at the interjacent C atom is conceivable, but much less stable than the formazan tautomers (Buemi et al, 1998) (see also Supplementary Figure S7). However, the transfer might occur via a proton wire mechanism, i.e., in a Grotthusstype fashion (Agmon, 1995;Miyake and Rolandi, 2015;Adams et al, 2021) as was found in water but also identified in other protic solvents (Stoyanov et al, 2008;Fujii et al, 2018;Long et al, 2020). Hence, the isomerization involving proton transfer should only be possible in protic solvents or in aprotic solvents containing at least traces of protic cosolvents.…”
Section: Interconnection Among Isomersmentioning
confidence: 89%
“…18 The latter undergo vehicular diffusion (Brownian motion). 19,20 In contrast, H 3 O + is subject to both Brownian motion and Grotthuss diffusion. The Grotthuss mechanism allows protons to rapidly migrate through water as a charge defect, by swapping covalent bonds for H-bonds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The transport properties of H 3 O + are unique, with a diffusion coefficient that is roughly 1 order of magnitude larger than that of other small cations such as Li + or Na + . The latter undergo vehicular diffusion (Brownian motion). , In contrast, H 3 O + is subject to both Brownian motion and Grotthuss diffusion. The Grotthuss mechanism allows protons to rapidly migrate through water as a charge defect, by swapping covalent bonds for H-bonds. Scheme indicates how this mechanism can result in H 3 O + translation along a H-bonded water wire. Liquid water contains an extensive branched network of such water wires because each H 2 O is ligated by ∼four other H 2 O molecules, albeit in a highly dynamic fashion. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations